Greenpeace's role in addressing the impact of fast fashion waste on the environment in Sub-Saharan Africa - Nurhandayani, Mulia (Universitas Islam Malang, 2025)
The fashion industry has experienced rapid growth along with the emergence of fast fashion. Fast fashion is a clothing business model that emphasizes rapid, large-scale production at affordable prices to meet trending needs. However, the emergence of fast fashion has caused a global environmental crisis worldwide, especially Africa being the most affected country. One of the ecological impacts of fast fashion is the increase in clothing waste. The increase in clothing waste has led Global North countries to systematically dispose of their used clothing in Ghana, Kenya, and Tanzania. This study aims to analyze the role of Greenpeace, an environmental NGO, in addressing the fast fashion waste crisis using the concept of Global Environmental Governance (GEG). The research method used is qualitative research with a case study approach. Data collection techniques include documentation studies from books, scientific journals, Greenpeace reports, online media, and others as data sources. The data obtained are then analyzed to draw research conclusions. The findings indicate that Greenpeace plays a significant role in global environmental governance. In the context of this research, Greenpeace has successfully raised the issue of fast fashion waste as part of the global political discourse. Greenpeace plays a role in (1) information provider, (2) input on agenda and policy developer, (3) environmental advocate, and (4) operational function implementer in the case of fast fashion waste in Ghana, Kenya, and Tanzania.